Elementary Level Kanji Games for Student at High School of Muhammadiyah 2 Sidoarjo - Fanani, Urip Zaenal; Soepardjo, Djodjok; Mintarsih, Mintarsih; Sopaheluwakan, Yovinza Bethvine; Parnaningroem, Raden Roro Dyah Woroharsi (Proceeding of International Joint Conference on UNESA, 2025)
Kanji instruction is frequently perceived by students as difficult and tedious, leading to low motivation and poor comprehension in learning the Japanese language. High School of Muhammadiyah 2 Sidoarjo is committed to addressing this challenge by developing innovative and interactive teaching methods through elementary-level Kanji games. The objectives of this Community service project are: (1) To enhance students’ understanding and mastery of elementary-level Kanji, (2) To boost student motivation through enjoyable learning methods, (3) To build students’ cognitive and social skills through interactive activities, and (4) Strengthen the relationship between teachers, students, and the school community in the learning process. The methodology employed includes: (1) Development of Kanji Games by creating various engaging and educational Kanji games, such as flashcard games, puzzles, and board games; (2) Classroom Implementation by integrating these Kanji games into the daily curriculum through structured play sessions; and (3) Evaluation and Feedback by conducting routine evaluations to measure the games’ effectiveness in improving students’ Kanji comprehension and collecting feedback for continuous improvement. The anticipated contributions this community service is: (1) Learning Innovation by introducing an innovative and interactive teaching method that makes learning Kanji more appealing, and (2) Increased Participation by promoting active student engagement in the learning process through fun activities. The benefits of this community service are expected to strengthen students’ comprehension of Kanji characters through repetition and application in an enjoyable context, boost students’ motivation and interest in learning Japanese, and hone cognitive skills such as memory, logic, and problem-solving.